VALIDITY AND RELIABILITY: PEDAGOGICAL ADAPTABILITY AND CONTEXTUAL DIGITAL LEARNING INSTRUMENT FOR TEACHERS IN THE NKRI–RDTL BORDER AREA - Yunawati Sele; Vinsensia Ulia Rita Sila; Frengky Neolaka (Universitas Labuhanbatu, 2026)
Purpose –This study aimed to develop and examine the validity and reliability of pedagogical adaptability and contextual digital learning development instruments for senior high school teachers in the NKRI-RDTL border area.Methodology – This study employed a quantitative approach using an instrument development research design. The study involved 64 senior high school teachers and four expert validators. Instrument development was carried out through the stages of theoretical construct development, indicator and item blueprint formulation, expert validation, instrument revision, field testing and validity and reliability analysis. Content validity was analyzed using Aiken’s V, empirical validity was analyzed using Pearson Product-Moment correlation, and instrument reliability was analyzed using Cronbach’s Alpha.Findings – The findings showed that the developed instruments had high content validity, with Aiken’s V values ranging from 0.88 to 1.00. The empirical validity test showed that most statement items were valid, while the reliability of both instruments was categorized as high to very high. These findings indicate that the developed instruments are appropriate for measuring pedagogical adaptability and contextual digital learning development in border areas.Contribution – The novelty of this study lies in the development of instruments designed based on the characteristics of learning in border areas, particularly in relation to the demands of adaptive and contextual digital learning. The developed instruments can be used as assessment tools to map teachers’ personal capacities more accurately and to support teacher competency development programs in border areas.